2021
DOI: 10.3390/plants10112484
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Provides Novel Insights into the Blanched Stem of Oenanthe javanica

Abstract: In the agricultural field, blanching is a technique used to obtain tender, sweet, and delicious water dropwort stems by blocking sunlight. The physiological and nutritional parameters of blanched water dropwort have been previously investigated. However, the molecular mechanism of blanching remains unclear. In the present study, we investigated transcriptomic variations for different blanching periods in the stem of water dropwort (pre, mid, post-blanching, and control). The results showed that many genes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…We also reported that the higher antioxidant capacity of blanched water dropwort was due to the higher content of vitamins and soluble sugars [2]. Another study by reported that a significant number of the genes were found downregulated in photosynthesis-related pathways that eventually reduced the chlorophyll content in water dropwort due to blanching [10]. Our previous study also reported that blanched samples contained the upregulation of many genes in the plant hormone signal transduction pathways and transcription factors, such as ERF, bHLH, MYB, and zinc finger.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We also reported that the higher antioxidant capacity of blanched water dropwort was due to the higher content of vitamins and soluble sugars [2]. Another study by reported that a significant number of the genes were found downregulated in photosynthesis-related pathways that eventually reduced the chlorophyll content in water dropwort due to blanching [10]. Our previous study also reported that blanched samples contained the upregulation of many genes in the plant hormone signal transduction pathways and transcription factors, such as ERF, bHLH, MYB, and zinc finger.…”
Section: Introductionmentioning
confidence: 59%
“…The RNA quality and quantity were determined with BioDrop uLite (80-3006-51). The cDNA library construction and transcriptomic sequencing were performed by Biomarker Technologies (Beijing, China) (http://www.biomarker.com.cn/, accessed on 4 February 2021) on the Illumina HiSeq 2000 platform [4,10,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations